Dynamic Mechanical Characteristics of Fractured Rock Reinforced by Different Grouts. (29th January 2021) - Kao, Siming; Zhao, Guangming; Meng, Xiangrui; Li, Yingming; Liu, Zenghui; Zhang, Ruofei; Zhou, Jun; Huang, Shunjie
Abstract : In order to investigate the dynamic mechanical properties of the fractured rocks reinforced with different slurries, the prefractured and grouted sandy mudstone specimens were tested on a Split Hopkinson Pressure Bar (SHPB), and their dynamic failure processes were shot via a high-speed camera. The test results showed that under dynamic loading, grouting reinforcement can relieve the rock failure at the fracture part. With the increase of the impact speed, the dynamic specific strength of the modified epoxy resin grouting increases from 0.85 to 1.01, and its specific strain rate increases from 1.09 to 1.04; the dynamic specific strength and specific strain rate of cement slurry grouting increase from 1.78 to 0.95 and from 0.60 to 0.98, respectively. As a whole, the specimen reaches or approaches the dynamic parameters of the intact rock specimen after grouting repair, the stability of the rock reinforced by modified epoxy resin grouting is superior to that of the rock reinforced by cement slurry grouting, and the latter can acquire high dynamic strength under low-speed impact. The improved damage-type Zhuwangtang (ZWT) model can be used to describe the dynamic mechanical behaviors of the fractured rocks reinforced by grouting very well.